Foot and Ankle Exercises Sebagai Upaya Pencegahan Komplikasi Neuropati pada Penderita Diabetes Mellitus - Muhtar; Julhana; Aniharyati; Dian Vitasari; Indra Rahmad; Ahmad (CV. CENDIKIA JENIUS INDONESIA, 2026)
This community service activity aimed to prevent neuropathy complications in patients with diabetes mellitus through the implementation of Foot and Ankle Exercises in Panda Village, Bima Regency. The program was carried out in three stages: training for assisting students, education and training for 10 health cadres, and training for 38 type II diabetes patients. Each stage included Ankle Brachial Index (ABI) and blood glucose examinations as indicators of success. The results showed a significant improvement in the knowledge and skills of both cadres and patients. Before the intervention, 90% of cadres and 74% of patients had low knowledge levels, but after the program, 80% of cadres and 68.43% of patients achieved good knowledge. The patients’ ABI scores also improved, with the number of borderline perfusion scores decreasing from 11 to 6 individuals, while normal scores increased from 27 to 32. These findings demonstrate that education and training on Foot and Ankle Exercises are effective in enhancing knowledge, practical skills, and the prevention of neuropathic complications among diabetes mellitus patients in Panda Village, Bima Regency.